Notary Role in The Implementation of The Registration of Legal Services Through Integrated Electronic Based on PP No 24 of 2018 - Mega Chandra Sera; Tito Dwi Anggoro; Munsharif Abdul Chalim (Jurnal Akta, 2018)
Notary as the competent authority in the incorporation through Single Submission Online system is a system that integrates all licensing services sought under the authority of the Minister / Chairman of agency governors, regents / mayors made through electronics. The purpose of this study was to determine the role of notaries in the registration of legal entities through a single online submission as well as the challenges and solutions faced in the electronic registration of legal entities. The method used in the study of the approach in this paper is normative, the specification of this research is descriptive. Source data using secondary data. Data collection techniques using literature study or studies document. Data were analyzed using qualitative descriptive approach. The result of the conclusion of the first and second. The role of the Notary in Online registration single submission is in this case is a deed, the ratification of legal entities and registration of business entities through AHU / SABU and obstacles role of notaries in the registration of Online Single Submission in PP No. 24 in 2018 does not regulate the role of a notary for registration of legal entities the solution of these obstacles as a notary public officials are required to understand the process of incorporation through a single online submission in the form of service is not authorizedKeywords: Notary; Single Online Submission; A Legal Entity.